2020
DOI: 10.1016/j.tranon.2020.100822
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying DNA damage induced by ionizing radiation and hyperthermia using single DNA molecule imaging

Abstract: Ionizing radiation (IR) is a common mode of cancer therapy, where DNA damage is the major reason of cell death. Here, we use an assay based on fluorescence imaging of single damaged DNA molecules isolated from radiated lymphocytes, to quantify IR induced DNA damage. The assay uses a cocktail of DNA-repair enzymes that recognizes and excises DNA lesions and then a polymerase and a ligase incorporate fluorescent nucleotides at the damage sites, resulting in a fluorescent “spot” at each site. The individual fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…Later, a dye (YOYO-1) was used to stain the DNA backbone and individual DNA molecules were stretched on silanized glass coverslips, where image analysis determined the extent of DNA damage by quantifying the incorporation of repaired bases on the single DNA molecule level ( cf . Figure 9C ) ( 51 , 63–65 ). PBMCs were exposed to Cu(II)–TC1 and intracellular SSBs were quantified (Figure 9d ).…”
Section: Resultsmentioning
confidence: 99%
“…Later, a dye (YOYO-1) was used to stain the DNA backbone and individual DNA molecules were stretched on silanized glass coverslips, where image analysis determined the extent of DNA damage by quantifying the incorporation of repaired bases on the single DNA molecule level ( cf . Figure 9C ) ( 51 , 63–65 ). PBMCs were exposed to Cu(II)–TC1 and intracellular SSBs were quantified (Figure 9d ).…”
Section: Resultsmentioning
confidence: 99%
“…ChIP-seq analysis showed that cells depleted of Pfh1 not only experience replication fork stalling, but also increased DNA damage as detected by γ-H2A, a marker of DNA damage ( 46 ). To determine if G4 stabilization by PhenDC3 causes ssDNA damage in S. pombe , we measured the formation of DNA lesions in PhenDC3-treated MDRΔ cells using a DNA damage detection assay based on imaging of single DNA molecules ( 43 , 44 ). In this DNA damage detection assay, we labeled the ssDNA breaks formed in genomic DNA isolated from PhenDC3-treated and untreated MDRΔ (YJJ21) cells (Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…The base excision repair (BER) pathway repairs base lesions caused by for instance oxidation, alkylation and deamination. Recently, a BER-based single-molecule imaging technique was used to identify and quantify ionizing radiation-induced single-stranded DNA (ssDNA) lesions ( 43 ). This technique identifies different types of DNA damages caused by DNA damaging agents based on proficiency of a particular enzyme in a BER enzyme mixture ( 43 , 44 ).…”
Section: Introductionmentioning
confidence: 99%
“…The ability of heat to interfere with the function of various DNA repair mechanisms (e.g., homology-directed repair, nonhomologous end-joining, base-excision repair) are known to greatly contribute to the efficacy of DNA-damaging therapies, including chemo and radiotherapy [ 115 ]. Heat may further amplify these effects by inducing various types of DNA damage, including nucleotide modifications and even, albeit controversially, DNA double-strand breaks (DSBs) [ 112 , 116 , 117 , 118 ]. In conclusion, mild HT affects various nuclear processes and sensitizes tumor cells to DNA-damaging therapies.…”
Section: The Biological Effects Of Hyperthermiamentioning
confidence: 99%